Avaliação energética, ambiental e econômica de bombas de cavidades progressivas com rotores produzidos a partir de diferentes materiais - Souza, Marcelo Angelo Taparello de (Universidade do Vale do Rio dos Sinos, 2019)
Progressive cavity pumps (PCPs) emerged in 1920 and are recent equipment compared to other fluid pumping technologies. In 1970, PCPs began to be used to the artificial elevation of petroleum, where they experienced a significant leap of technological recognition and the awakening to other applications in the industry. Among them, as of 2000, in dosing machines of the tinting industry for dosing of concentrated colorants. In this application, PCPs difficultly totaling one hundred continuous hours of use. However, in general industry applications, pumps work for thousands of hours, often under severe conditions, pumping abrasive fluids, operating at high pressures, undergoing chemical attack. In this context, alternative materials were explored for components of PCPs used in tinting, given the low demand they experience. This work, through a methodology with experimental focus, carried out an energetic, environmental and economical evaluation of four different materials for the rotor of a BCP: the traditional chromium-coated steel, PA6, PEEK and aluminum alloy 6082. An equipment was built for the experimental tests and the characteristic curves of each PCP were obtained, evaluating the electric energy consumption, rotors and stators wear and pump energy efficiency. Electrical energy and inputs from the rotor manufacturing process were evaluated. Finally, we applied the environmental management tools Cleaner Production and LCIA aided by CES EduPack software and an economic evaluation of the rotors was carried out. The materials studied for the rotor met the requirements of durability in the application of the tinting industry, and did not present a functional failure of the equipment at the end of the test period. The results showed that the studied polymers had no incompatibility with the working fluid. No significant wear was identified on the stator-rotor pairs and the minimum lifetime did not challenge the integrity of the components. The best and worst energy efficiency of the BCPs were with alloy 6082 and PA6 rotors, respectively, presenting a difference of 22.5% in electric energy consumption. However, the PA6 rotor presented the best energy and environmental efficiency in the manufacturing process, besides being the only one with dry machining capacity. All proposed materials reported economic improvements, where the alloy 6082 and PA6 rotors exceed 90% cost reduction.
Keywords: Tintometria; Bomba de cavidades progressiva; Eficiência energética; Usinagem; Turbilhonamento; Impacto ambiental; Tinting; Progressive cavity pump; Energy efficiency; Machining; Whirling; Environmental impact; ACCNPQ::Engenharias::Engenharia Mecânica